(untitled) (International Journal of Environmental Sciences, 2025)
This study examines multi-actor collaboration in implementing data-driven village development systems in Bantaeng Regency, Indonesia, where despite high village development indices, only 4.3% of villages have adopted digital mapping technologies. Using Kingdon’s Multi-Actor Theory and Multiple Streams Framework, this qualitative case study analyzed the roles of government actors (regency head, bureaucratic agencies, legislative bodies, village governments) and outside government actors (academics, private sector, media, civil society) through in-depth interviews, direct observation, and document analysis. The findings reveal significant coordination challenges between hierarchical government structures and diverse stakeholder interests, with village-level implementation enthusiasm constrained by absent regency-level regulatory frameworks and limited systematic engagement from outside government actors. While successful pilot implementations in Patteneteang and Biangloe villages demonstrate clear benefits including enhanced transparency, improved planning accuracy, and better service delivery, the absence of formal multi-stakeholder coordination mechanisms prevents systematic scaling across all villages. The analysis through the Multiple Streams Framework shows that despite adequate problem identification and available policy solutions, insufficient political stream coordination limits the emergence of effective policy windows for comprehensive implementation. The study concludes that establishing regency-level multi-stakeholder governance platforms with dedicated regulatory backing and budget allocation would enhance coordination effectiveness and accelerate systematic adoption of data-driven village development initiatives across Indonesian rural contexts